Relationship between lipid profiles and reduced handgrip strength (dynapenia) in hospitalized patients with cirrhosis. Issue 5 (18th May 2023) - Cui, Binxin; Hui, Yangyang; Sun, Chao
Abstract : Background: Dynapenia embraces clinical significance and predictive value separated from skeletal muscle loss among cirrhosis. Moreover, alterations in lipid levels may impact muscle function. It has yet to elucidate the relationship between lipid profiles and muscle strength weakness. We sought to explore which lipid metabolism indicator could be useful to identify patients with dynapenia in daily practice. Methods: A retrospective observational cohort study enrolling 262 cirrhotic patients. Analysis of the receiver operating characteristic (ROC) curve was performed to determine the discriminatory cutoff for dynapenia. Multivariate logistic regression was conducted to assess the association between total cholesterol (TC) and dynapenia. Also, we established a model based on the classification and regression tree method. Results: ROC implicated a cutoff of TC ≤ 3.37 mmol/L to identify dynapenia. Patients with TC ≤ 3.37 mmol/L showed significantly lower handgrip strength (HGS; 20.0 vs. 24.7 kg, P = 0.003), lower hemoglobin, lower platelet, lower white blood cell count, lower sodium and higher prothrombin-international normalized ratio. A positive correlation was found between TC and HGS values ( r = 0.1860, P = 0.003). TC remained a significant association with dynapenia after controlling for variables including age, sex, BMI, and the presence of ascites. The decision tree incorporating TC, BMI, and age had a sensitivity of 71.4%, specificity of 64.9%, and an area under ROC of 0.681. Conclusion: TC ≤ 3.37 mmol/L was significantly associated with the presence of dynapenia. Assessing TC may be helpful for identifying dynapenic patients with cirrhosis in the health care or hospital setting.